Principals’ administrative skills in public senior secondary schools: A case of Ilorin Nigeria - Akinnubi, Olaolu Paul; Owonwami, Olabisi Aminat; Olaiya, Salmon Naallah (Journal of Educational Management and Instruction (JEMIN), 2023)
Implementation of administrative skills by secondary school principals plays an inevitable role towards the attainment of educational goals and objectives. This study investigated principals' administrative skills implementation in public senior secondary schools in Ilorin Metropolis of Kwara State on the indicators of principals’ financial and physical facilities maintenance and interpersonal relationship skills. The study adopted a descriptive survey. One hundred teachers were randomly selected from public senior secondary schools in Ilorin Metropolis as a sample. The researcher instrument titled Assessment of Principals’ Administrative Skills Questionnaire (APASQ) was used for data collection. Two research questions were raised and answered to guide the conduct of the study. Descriptive statistics were used to answer the research questions raised. Findings showed that 28.8% constituted the majority of the respondents who agreed that principals had financial skills in Ilorin Metropolis. Results indicated that 45.6% constituted the majority of the respondents who strongly agreed that principals had physical facilities maintenance skills. It was shown that 42% constituted the majority of the respondents who strongly agreed that their principals had interpersonal relationship skills. Findings revealed that 68% constituted the majority who agreed that the level of principals’ administrative skills in public senior secondary schools in Ilorin Metropolis was high. It was recommended among others that principals endeavour to keep a high level of professional spirit and good moral standards in the schools to adopt their administrative skills to sustain a good working environment for teachers and other staff in their schools.